Progress in modeling and simulation - Kindler, E (Sbornik lekarsky, 1998)
For the modeling of systems, the computers are more and more used while the other "media" (including the human intellect) carrying the models are abandoned. For the modeling of knowledges, i.e. of more or less general concepts (possibly used to model systems composed of instances of such concepts), the object-oriented programming is nowadays widely used. For the modeling of processes existing and developing in the time, computer simulation is used, the results of which are often presented by means of animation (graphical pictures moving and changing in time). Unfortunately, the object-oriented programming tools are commonly not designed to be of a great use for simulation while the programming tools for simulation do not enable their users to apply the advantages of the object-oriented programming. Nevertheless, there are exclusions enabling to use general concepts represented at a computer, for constructing simulation models and for their easy modification. They are described in the present paper, together with true definitions of modeling, simulation and object-oriented programming (including cases that do not satisfy the definitions but are dangerous to introduce misunderstanding), an outline of their applications and of their further development. In relation to the fact that computing systems are being introduced to be control components into a large spectrum of (technological, social and biological) systems, the attention is oriented to models of systems containing modeling components.
Keywords: teoretické modely; Models, Theoretical; programovací jazyk; počítačová simulace; Computer Simulation; Programming Languages